The phenomenon of legal regulation of business activities - Marukyan, G. (IJRDO - Journal of Business Management, 2017)
In the conditions of developing market economy, when the planned economy was gradually replaced form capitalistic society into free market economy, proper legislative regulation of business relations became of great importance. The changes had their immediate impact on the legal regulatory mechanisms of the society structured economic sector as well. The legal definition of business relations, their proper regulations came to be of greatest importance. The legal definition of business activities in itself has some problems, concerning the fact, that within the framework of the definition, defined as "entrepreneurial", and activities based on risk, the regulatory mechanism defines as business activity the one having the aim to gain profit, the one, which can be defined as business activity, even if the person is qualified as such activity is carried out only once. It comes clear, that in accordance with the present legal regulation, person’s can be considered as business activity even if one had done the action once in his/her life. This definition may cause many problems in practice. Within the article, with the help of comprehensively analyze and based on scientifically substantiated opinions on the issue, new ways of improving legislation are presented